RING-Domain E3 Ligase-Mediated Host–Virus Interactions: Orchestrating Immune Responses by the Host and Antagonizing Immune Defense by Viruses - Zhang, Yuexiu; Li, Lian-Feng; Munir, Muhammad; Qiu, Hua-Ji (Frontiers in Immunology, 2018)
The RING-domain E3 ligases (RING E3s), a group of E3 ligases containing a RING finger domain, are involved in various cellular processes such as cell proliferation, immune regulation, apoptosis among others. In the host, a substantial number of the RING E3s have been implicated to inhibit viral replication through regulating immune responses, including activation and inhibition of RIG-I-like receptors, Toll-like receptors and DNA receptors signaling pathways, modulation of cell-surface expression of major histocompatibility complex and co-stimulatory molecules. During the course of evolution and adaptation, viruses encode RING E3s to antagonize host immune defense, such as the infected cell protein 0 of herpes simplex virus type 1, the nonstructural protein 1 of rotavirus and the K3 and K5 of Kaposi’s sarcoma-associated herpesvirus. In addition, recent studies suggest that viruses can hijack the host RING E3s to facilitate viral replication. Based on emerging and interesting discoveries, the RING E3s present novel links among the host and viruses. Herein, we focus on the latest research progresses in the RING E3s-mediated host-virus interactions and discuss the outlooks of the RING E3s for future research.